Sexual reproduction and mating-type-mediated strain development in the penicillin-producing fungus Penicillium chrysogenum - Böhm, Julia; Hoff, Birgit; O'Gorman, Céline M.; Wolfers, Simon; Klix, Volker; Binger, Danielle; Zadra, Ivo; Kürnsteiner, Hubert; Pöggeler, Stefanie; Dyer, Paul S.; Kück, Ulrich (National Academy of Sciences, 2013)
Penicillium chrysogenum is a filamentous fungus of major medical and historical importance, being the original and present-day industrial source of the antibiotic penicillin. The species has been considered asexual for more than 100 y, and despite concerted efforts, it has not been possible to induce sexual reproduction, which has prevented sexual crosses being used for strain improvement. However, using knowledge of mating-type (MAT) gene organization, we now describe conditions under which a sexual cycle can be induced leading to production of meiotic ascospores. Evidence of recombination was obtained using both molecular and phenotypic markers. The identified heterothallic sexual cycle was used for strain development purposes, generating offspring with novel combinations of traits relevant to penicillin production. Furthermore, the MAT1-1–1 mating-type gene, known primarily for a role in governing sexual identity, was also found to control transcription of a wide range of genes with biotechnological relevance including those regulating penicillin production, hyphal morphology, and conidial formation. These discoveries of a sexual cycle and MAT gene function are likely to be of broad relevance for manipulation of other asexual fungi of economic importance.